G-autonomy of EEG recordings of psychotic patients undergoing the primitive expression form of dance therapy. (August 2015) - Ventouras, E-C; Lardi, I; Dimitriou, S; Margariti, A; Chondraki, P; Kalatzis, I; Economou, N-T; Tsekou, H; Paparrigopoulos, T; Ktonas, P Y
Abstract: Primitive expression (PE) is a form of dance therapy (DT) that involves an interaction of ethologically and socially based forms which are supplied for re-enactment. Brain connectivity has been measured in electroencephalographic (EEG) data of patients with schizophrenia undergoing PE DT, using the correlation coefficient and mutual information. These parameters do not measure the existence or absence of directionality in the connectivity. The present study investigates the use of the G-autonomy measure of EEG electrode voltages of the same group of schizophrenic patients. G-autonomy is a measure of the "autonomy" of a system. It indicates the degree by which prediction of the system's future evolution is enhanced by taking into account its own past states, in comparison to predictions based on past states of a set of external variables. In the present research, "own" past states refer to voltage values in the time series recorded at a specific electrode and "external" variables refer to the voltage values recorded at other electrodes. Indication is provided for an acute effect of early-stage PE DT expressed by the augmentation of G-autonomy in the delta rhythm and an acute effect of late- stage PE DT expressed by the reduction of G-autonomy in the theta and alpha rhythms.